Nitrites and nitrates from food additives and cancer risk: results from the NutriNet-Santé cohort. (20th October 2021) - Chazelas, E; Pierre, F; Druesne-Pecollo, N; Gigandet, S; Srour, B; Huybrechts, I; Julia, C; Kesse-Guyot, E; Deschasaux-Tanguy, M; Touvier, M
Abstract:  : Nitrates and nitrites occur naturally in water and soil and are commonly ingested from water and dietary sources. They are also frequently used as food additives mainly in processed meats. Experimental data consistently suggest their involvement in carcinogenesis but human data is still limited. The aim was to investigate the relationship between nitrate and nitrite intakes and the risk of cancer in a large prospective cohort with detailed and up-to-date dietary assessment. Overall, 101, 056 adults from the French NutriNet-Santé cohort study (2009-ongoing) were included. Consumption of nitrites and nitrates was evaluated using repeated 24h dietary records, linked to a comprehensive food composition database which includes details of commercial names/brands of industrial products. Prospective associations between nitrite and nitrate exposures and the risk of cancer were assessed by multivariable Cox hazard models. During follow-up, 3311 first incident cancer cases were diagnosed. Compared with non-consumers, higher consumers of nitrates as food additives had higher risk of breast cancer (HR = 1.24 (1.03-1.48), P = 0.02); this was more specifically observed for potassium nitrate e252, P = 0.01). Higher consumers of nitrites as food additives, and specifically for sodium nitrite (e250), had a higher risk of prostate cancer (HR = 1.58 (1.14-2.18), P = 0.008 and HR = 1.62 (1.17-2.25), P = 0.004, respectively). No significant association was observed for nitrates and nitrites from natural sources. In this large prospective cohort, nitrates as food additives were positively associated with breast cancer risk and nitrites as food additives were positively associated with prostate cancer risk. While these results need confirmation in other large-scale prospective studies, they provide new insights in a context of lively debate around the ban of nitrite additives in food products. Key messages: Nitrates as food additives were positively associated with breast cancer risk. Nitrites as food additives were positively associated with prostate cancer risk.